Proses Adaptasi Sosio-Kultural Perantau Menghadapi Pandemi Covid-19 (Studi Kasus : Penghuni Rumah Kontrakan “Morotai No. 4” di Desa Dauh Puri Klod, Kecamatan Denpasar Barat, Kota Denpasar) - Mohammad Mas Adi Fitrah Indarwan; I Nyoman Suarsana; I Ketut Kaler (Sunari Penjor : Jurnal of Anthropology, 2022)
Adaptation is a process of human adjustment to the natural environment that has not yet been completed exploring the world of they live. The Covid-19 pandemic that has hit the entire world, forced the Province of Bali to have to sacrifice the tourism sector which has been the main source of the economy since the era of the Dutch East Indies Colonial Government. The absence of tourists who can visit Bali Province makes the people of Denpasar City have to rack their brains to formulate steps to adapt to changing times, including the immigrants. There are several immigrants who still survive in the city of Denpasar to face Covid-19 pandemic, one of the residents of the rented house "Morotai No. 4”. This study aims to decide the socio-cultural adaptation process carried out by immigrants in Denpasar City in the face of the Covid-19 pandemic through a case study by residents of the rented house "Morotai No. 4” in Dauh Puri Klod Village, West Denpasar District, Denpasar City. This research approach uses descriptive qualitative. With models. This research is expected to show the facts that occur in the field from a number of events and existing phenomena.